Revitalizing the Importance of Community Leaders' Role in Preventing Conflicts During the COVID-19 Pandemic - Suneki, Sri; ., Haryono (KnE Social Sciences, 2022)
The world is currently experiencing a downturn due to the COVID-19 pandemic that has significantly triggered a variety of problems in our society today. These problems have the potential to create conflict and lead to conflicts of interest among people of different groups. Various vulnerabilities arise with issues of virus spread, information dissemination, and the sensitivity of people who are experiencing changes in the new life order in terms of lifestyle, communication, social interactions, civic commitment, and responsiveness to the environment. Changes in the value order of social humanists will shift to a more structural and individualist opposition. The situation is getting complicated and the problem of conflict is getting widespread, it must be suppressed so that it will subside. The participation of the entire community is important. One of its strengths is the presence of community leaders who contribute as motivators and problem solvers in society. This research uses a qualitative design that focuses on revitalizing the role of community leaders in preventing conflict. The results show that strengthening the role of community leaders is very urgent in preventing conflict during the COVID-19 pandemic through a social resilience approach, as a mediator of ”Jogo Tonggo,” as well as a facilitator in conflict resolution. Keywords: community leaders, conflict, COVID-19 pandemic